PERKEMBANGAN HUKUM ISLAM DARI MASA KERAJAAN DI INDONESIA - Imam Makmun; Lomba Sultan; Kurniati (CV. Ulil Albab Corp, 2022)
Islamic law is divine rules that were entrusted to the Prophet Muhammad SAW to be conveyed to mankind, especially to his people, both legal rules in the form of belief and legal rules related to a deed. The previous scholars played a large role in the process of developing Islam in Indonesia. Therefore we must maintain the results of the thoughts of our predecessors whose thoughts were not carried out arbitrarily but with ijtihad which was not easy. Factors that support the use of Islamic law in Indonesia include Islam as a religion with the majority of adherents being a promising asset. Then another supporting factor lies in the broad scope of the legal field. The factors that hinder the acceptance of Islamic law in Indonesia consist of internal and external factors. Internal factors stem from the lack of maximum institutionalization and a dichotomous view of Islamic law. Meanwhile, the external factor is the influence of the government's legal politics on certain legal fields